An Interesting Fistula Tract Presenting with Recurrent Gluteal Abscess: Instructive Case - Gulsum Iclal Bayhan; Ozge Metin; Burak Ardicli; Ayse Karaman; Gonul Tanir (Hindawi Limited, 2015)
A fistula extending from the gluteus to penis is an extremely rare entity. In this paper, we have highlighted novel variant of congenital penile to gluteal fistula complicated with gluteal and penoscrotal abscess in a previously healthy boy. A fistulous tract extending from the gluteus to penis has been shown by fistulogram. Bleomycin has been used in fistula tract with successful results in our patient.